The Role of Inspiring Value Process: Customer Participation and Marketing Performance - Panjaitan, Roymon; Putra, Febrianur Ibnu Fitroh Sukono; Fatmawati, Elia Resha; Sobirov, Bobur (Universitas Bangka Belitung, 2025)
This exploratory study aims to fill the research gap on unanswered findings in the Service-Dominant Logic (SDL) approach from the role of the inspiring value process. The novelty of this study's model framework is rooted in the SDL perspective that an inspiring value process will achieve shared value creation from the support of customer participation. In the end, this inspiration can shape values from product-centered to service-centered. Four hypotheses were developed and tested using PLS-SEM analysis techniques within a sample frame of 175 MSMEs in Central Java, Indonesia. The findings of this investigation produce four conceptual contributions. Firstly, customer participation has been proven not to impact improving marketing performance positively, but marketing performance can increase when bridged by an inspiring value process from customer participation. Thirdly, customer participation can provide leverage to inspire process value. Fourthly, the inspiring value process directly contributes positively to increasing marketing performance. Conceptual implications provide new propositions that can bridge inconsistencies in findings and empirical results, proving the role of the inspiring value process in contributing practically and theoretically to the SDL perspective